Development E-Module of Process Oriented Guided Inquiry Learning on Thermochemistry - Simangunsong, Garvin Brilly Anugerah; Purba, Jamalum (Jurnal Inovasi Pembelajaran Kimia, 2025)
This study aims to develop a thermochemistry e-module based on Process Oriented Guided Inquiry Learning (POGIL) for Grade XI students at SMAN 14 Medan. Based on observations, thermochemistry is considered a difficult topic for students due to the lack of textbooks, learning resources, and appropriate learning media. This research is a development study using the 4D model (Define, Design, Develop, Disseminate). The developed e-module was validated by two chemistry lecturers and one chemistry teacher, and its practicality was tested by 31 students from class XI-3. The initial validation results showed a score of 89.7% for the material aspect and 85.05% for the media aspect, both categorized as very valid. After revisions, the scores increased to 91.8% for the material aspect and 90.8% for the media aspect. The practicality test based on students’ responses gained a score of 90.1%, indicating that the e-module is very practical for use in learning. Therefore, the POGIL-based thermochemistry e-module is proven to be valid and practical, and it effectively supports students’ interest and understanding in learning thermochemistry.